The effect of ageing on the blood-brain barrier: The potential of nanoparticle drug delivery systems to target cerebrovascular changes - Bates, Jessica (2025)
Within physiological ageing, recent evidence has shown that alterations to blood-brain barrier (BBB) permeability are potentially caused by a shift towards non-selective entry of systemic molecules into the brain via transcytosis. The ability to exploit this to deliver therapeutic molecules to target age-related changes of the BBB via lipid nanoparticles is an area of particular interest.